Common and Distinct Alterations of Cognitive Function and Brain Structure in Schizophrenia and Major Depressive Disorder: A Pilot Study - Ma, Mengying; Zhang, Yuyanan; Zhang, Xiao; Yan, Hao; Zhang, Dai; Yue, Weihua (Frontiers in Psychiatry, 2021)
Objective Numerous studies implicated that schizophrenia (SCZ) and major depressive disorder (MDD) shared pathophysiological characteristics. Investigating the neurobiological features of psychiatric-affective disorders may facilitate the diagnosis of psychiatric disorders. Hence, we aimed to explore whether patients with SCZ and patients with MDD had the similar or distinct cognitive impairments and GMV alterations for further understanding their underlying pathophysiological mechanisms. Methods We totally recruited 52 MDD patients, 64 SCZ patients and 65 healthy controls (HCs). The Measurement and Treatment Research to Improve Cognition in Schizophrenia (MATRICS) Consensus Cognitive Battery was used to assess the cognitive functions. Besides, voxel-based morphometry (VBM) analysis was used to evaluated the gray matter volume (GMV) by using the MRI scanning. One-way ANOVA and post hoc tests were used to find the differences among the MDD, SCZ and HCs. Finally, we explored the correlation between the structural alterations and cognitive functions. Results Compared with HCs, process of speed was impaired in both patients with SCZ and patients with MDD （F = 49.505, P < 0.001）. SCZ patients indicated impaired cognitive performance in all dimensions of cognitive functions compared with HCs (P < 0.001, except social cognition, P = 0.043, Bonferroni corrected). Whole brain VBM analysis showed that both SCZ and MDD groups had the reductions of GMV in the medial superior frontal cortex (voxel-level FWE P < 0.05). Patients with SCZ exhibited declined GMV in the anterior cingulate cortex and right middle frontal cortex (MFC) compared with HCs and MDD patients (voxel-level FWE P < 0.05). The mean values of GMV in the right MFC had a positive correlation with the attention/vigilance function in patients with MDD (P = 0.014, partial.r = 0.349, without Bonferroni correction). Conclusions Totally, our study found that MDD and SCZ groups had common cognitive impairments and brain structural alterations, but the SCZ group exhibited more severe impairments than the MDD group in both fields. The above findings may provide a potential support for recognizing the convergent and divergent brain neural pathophysiological mechanisms between MDD and SCZ.